Randomized clinical trial of the effect of a fibrin sealant patch on pancreatic fistula formation after pancreatoduodenectomy. Issue 7 (17th April 2018) - Schindl, M.; Függer, R.; Götzinger, P.; Längle, F.; Zitt, M.; Stättner, S.; Kornprat, P.; Sahora, K.; Hlauschek, D.; Gnant, M; ,
Abstract : Background: The potential for a fibrin sealant patch to reduce the risk of postoperative pancreatic fistula (POPF) remains uncertain. The aim of this study was to evaluate whether a fibrin sealant patch is able to reduce POPF in patients undergoing pancreatoduodenectomy with pancreatojejunostomy. Methods: In this multicentre trial, patients undergoing pancreatoduodenectomy were randomized to receive either a fibrin patch (patch group) or no patch (control group), and stratified by gland texture, pancreatic duct size and neoadjuvant treatment. The primary endpoint was POPF. Secondary endpoints included complications, drain‐related factors and duration of hospital stay. Risk factors for POPF were identified by logistic regression analysis. Results: A total of 142 patients were enrolled. Forty‐five of 71 patients (63 per cent) in the patch group and 40 of 71 (56 per cent) in the control group developed biochemical leakage or POPF ( P = 0·392). Fistulas were classified as grade B or C in 16 (23 per cent) and ten (14 per cent) patients respectively ( P = 0·277). There were no differences in postoperative complications (54 patients in patch group and 50 in control group; P = 0·839), drain amylase concentration ( P = 0·494), time until drain removal (mean(s.d.) 11·6(1·0) versus 13·3(1·3) days; P = 0·613), fistula closure (17·6(2·2) versus 16·5(2·1) days; P = 0·740) and duration of hospital stay (22·1(2·2) versus 18·2(0·9) days; P = 0·810) between the two groups. Multivariable logistic regression analysis confirmed that obesity (odds ratio (OR) 5·28, 95 per cent c.i. 1·20 to 23·18; P = 0·027), soft gland texture (OR 9·86, 3·41 to 28·54; P < 0·001) and a small duct (OR 5·50, 1·84 to 16·44; P = 0·002) were significant risk factors for POPF. A patch did not reduce the incidence of POPF in patients at higher risk. Conclusion: The use of a fibrin sealant patch did not reduce the occurrence of POPF and complications after pancreatoduodenectomy with pancreatojejunostomy. Registration number: 2013‐000639‐29 (EudraCT register). Abstract : Not effective in reducing complications